Removal of flocculated TiO2 nanoparticles by settling or dissolved air flotation. Issue 7 (21st March 2021) - Oliveira, H. A.; Azevedo, A.; Rubio, J.
ABSTRACT: Engineered nanoparticles of TiO2 (TiO2 -NPs) are used in the industry for a great number of applications. After their usage, the particles end up in aquatic environments, contaminating supply waters and watercourses. Bench-scale studies report removal of TiO2 -NPs (450 nm, the mean volumetric diameter) by flocculation followed by settling or by dissolved air flotation (4 bar saturation pressure and 30% recycling ratio). Floc formation was conducted after heterocoagulation with iron hydroxide (30–40 mg L −1  Fe 3+) and gelatinized corn starch (10–20 mg   L −1 ) as flocculant, at pH 7. Particle size distribution and zeta potential, removal efficiencies as a function of time and microphotography of flocs were analyzed. Mechanisms involve ferric hydroxide precipitation, heterocoagulation with the nanoparticles and flocculation of the loaded carrier precipitates with gelatinized starch. Best results showed removals between 95–100% of TiO2 -NPs, either by settling or flotation after 5 min. Clear treated waters with low turbidity < 3 nephelometric turbidity units (NTU) and TiO2 -NPs concentrations <1 mg L −1 were obtained. A practical advantage in DAF was the higher solids content (1.9% w/w) of the sludge, when compared to settling (0.7% w/w). This would facilitate the sludge dewatering and disposal, but DAF has the disadvantage of the poor efficiency at high concentration of the nanoparticles of titanium oxide (>100 mg L −1 ). Conversely, the removal by settling of the flocs increased at high dosages. It is believed that both processes are sustainable in terms of reagents and the removal efficiencies of TiO2 nanoparticles from water. GRAPHICAL ABSTRACT: UF0001